The sanctification of yiddish among Hasidim - Reiser, Daniel (AJS review, 2020)
The sanctification of Yiddish in hasidic society occurred primarily in the first half of the twentieth century and intensified in the wake of the Holocaust. The roots of this phenomenon, however, lie in the beginnings of Hasidism in the eighteenth century. The veneration of Yiddish is linked to the hasidic attitude towards vernacular language and the status of the ẓaddik “speaking Torah.” Hasidism represented—and represents—an oral culture in which the verbal transfer of its sacred content sanctifies the language spoken by its adherents, in this case, Yiddish. This article presents a theological and sociological examination of the various stages of the sanctification of Yiddish among Hasidim from the movement's early stages to the late twentieth century.